The study of bodily, mental, social , and economical problems of major ‎thalassemia infected patient that referred to Somesara Imam Khomeini Hospital - zahra majde teimoori; mitra sedghi sabet; farideh hasavari; mitra rezapuor (Guilan University of Medical Sciences, 2008)
Introduction: At present century, hereditary illnesses are most common illnesses of today ‎human. Our country, Iran from the ‎‏250‏‎ million patients affected to a type of hereditary ‎anemia in the world has the first rank. According to recent statistics, there are more than ‎‏30000‏‎ thalassemic patients in Iran. The important point is that most of these patients are in the ‎north provinces and their treatment costs are more than ‎‏35‏‎ million Rials per year. ‎ Objective: Study aims to determine physical, mental and socio-economic problems of ‎thalassemic patients referring to Emam Khomeini Hospital SomeaSara. ‎ Methods: In this descriptive analytic study all patients with Major thalasemia who referred to ‎thalassemia ward of Imam Khomeini Hospital in SomeaSara were selected in (‎‏77‏‎ individual) ‎and received necessary information by questionnaire. In this questionnaire in addition to ‎population characteristics, their physical, mental and socio-economic problems were assessed. ‎ Results: Study results showed that most physical problem (‎‏58.4%‏‎) included " largeness of ‎spleen and spleenectomy", most mental problem (‎‏51.9%‏‎) was " feeling in depression and ‎disappointment", most social problem included " long distance from place of living to health ‎center" and finally most economic problem (‎‏67.5%‏‎) included insufficient financial support of ‎Thalassemia Patient Protection Community. ‎ Conclusion: In general results of this research show that more than ‎‏50%‏‎ of thalassemia ‎patients suffer from physical, mental, and socio-economic problems. Therefore, since our ‎country has the highest rate of thalassemic patients and most of them are young, requires ‎better attention of those responsible in order to promote their quality of life and also decrease ‎the high costs. ‎